The security of using advanced materials: selected legal problems - Jurewicz, Marcin (Management and Administration Journal, 2019)
The aim of the article is to solve the problem to what extent the safety of using advanced materials is guaranteed by the legislator. The article refers to the basic legal acts concerning chemical substances in the form of nanomaterial and polymers: REACH Regulation and CLP Regulation. The applied research methods are: formal-dogmatic, that is analysis and interpretation of legal provisions and syllogistic, that is the theoretical, abstract way of reasoning and generalization of administrative law institutions. Advanced materials mean a set of techniques and processes aimed at researching and manipulating matter in order to better understand materials (including at atomic and molecular scale) so that the knowledge acquired in this way can be used in the production of new materials characterized by the desired structure and properties. Advanced materials serve the production of innovative products in numerous sectors for the benefit of society and have been recognized as key enabling technologies in the EU. In particular, the legal challenge is to guarantee the safety of using innovative applications of nanomaterials and polymers.